2015
DOI: 10.7314/apjcp.2015.16.6.2199
|View full text |Cite
|
Sign up to set email alerts
|

T-786C, G894T, and Intron 4 VNTR (4a/b) Polymorphisms of the Endothelial Nitric Oxide Synthase Gene in Bladder Cancer Cases

Abstract: The aim of the present study was to determine whether endothelial nitric oxide synthase (eNOS) gene polymorphisms play a role in development of bladder cancer in the Turkish population. The study was performed on 75 patients (64 men, 11 women) with bladder cancer and 143 healthy individuals (107 men, 36 women) with any kind of cancer history. Three eNOS gene polymorphisms (T-786C promoter region, G894T and intron 4 VNTR 4a/b) were determined with polymerase chain reaction and restriction fragment lenght polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…18 No association was identified for eNOS T-786C and intron 4 VNTR 4a/b polymorphisms between patients with bladder cancer and control groups in our Turkish population. 19 Analysis of the VNTR intron 4 polymorphisms in eNOS gene revealed that the frequency of the AA genotype was significantly higher in the control group, whereas the frequency of the BB genotype was significantly higher in the ECa group. Analysis of the G894T polymorphisms in eNOS gene revealed a significantly higher frequency of the GG genotype in the control group but a significantly higher frequency of the TT genotype in the endometrial cancer group.…”
Section: Discussionmentioning
confidence: 97%
“…18 No association was identified for eNOS T-786C and intron 4 VNTR 4a/b polymorphisms between patients with bladder cancer and control groups in our Turkish population. 19 Analysis of the VNTR intron 4 polymorphisms in eNOS gene revealed that the frequency of the AA genotype was significantly higher in the control group, whereas the frequency of the BB genotype was significantly higher in the ECa group. Analysis of the G894T polymorphisms in eNOS gene revealed a significantly higher frequency of the GG genotype in the control group but a significantly higher frequency of the TT genotype in the endometrial cancer group.…”
Section: Discussionmentioning
confidence: 97%
“…The NOS family includes three isoenzymes: eNOS, inducible NOS (iNOS), and neuronal NOS (nNOS). eNOS is expressed in endothelial cells, and genetic polymorphisms of eNOS have been extensively studied in erectile dysfunctions (Lee et al, 2009b) and cancers, such as PCa and bladder cancer (Wartenberg et al, 2003;Tong and Li, 2004;Zhang et al, 2014;Polat et al, 2015). Deregulated eNOS was found to be associated with aging and several cancers, such as pancreatic cancer and PCa (Nanni et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although, there were studies that the eNOS G894T variant was associated with prostate cancer, bladder cancer, colorectal cancer, larynx cancer, there were studies that the eNOS G894T variant was not associated with cancer and survival. 4,5,7,[39][40][41][42] Lee et al declared that there was no significant associa-International Journal of Hematology and Oncology tion between the eNOS G894T variant and breast cancer, but this variant was associated with lymph node involvement. 43 In present study, we found a significant difference in genotype distribution between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In studies for cancer suspectibility, it was found that eNOS 4 a/b variant is associated with colorectal cancer, prostate cancer, whereas there was no significant association with bladder cancer and overall cancers. 4,7,10,37,38 In sub-group analysis based on ethnicity of meta analysis, it was reported that the eNOS 4 a/b variant was associated with an increased risk of cancer in Caucasians. 24 In our study, we found that the the eNOS intron 4 a/b variant wasn't significantly different between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation